Building environmental resilience: A snapshot of farmers adapting to climate change in Kenya - Thomson, K.; Kruszewska I; Tirado R (Greenpeace Research Laboratories, 2015)
This report provides insight into the organisations (including CGIAR Research Program on Climate Change, Agriculture and Food Security - East Africa) and initiatives working to build resilience in agriculture in Kenya. During October 2014, a Greenpeace team (Iza Kruszewska and Reyes Tirado) visited farmers in West and Central Kenya and the local organisations working alongside them. We interviewed farmers and local institutional partners to better understand the adaptive practices, and reflect on their effectiveness building resilience and improving farmers’ livelihoods in the face of changing weather patterns. What follows is a summary of the cases in light of their significance as ‘climate-resilient farming’, trying to represent farmers’ insights into practices that, in their views and based on our reflections, will help them adapt to a changing climate and support their rural livelihoods. Each farmer’s case is presented with information on the adaptive practices and the local or community institution that they work in collaboration with (a table listing farm locations and local organisations visited by the Greenpeace team can be found in Annex I).